Peran Konten Kreatif dan Interaksi Online dalam Meningkatkan Loyalitas Pelanggan UMKM - amalia, nur zaibi (Maliki Interdisciplinary Journal, 2026)
The role of creative content and online interaction in enhancing customer loyalty among SMEs in the digital era. Creative content serves as an initial trigger that attracts attention and builds brand awareness, while online interaction strengthens emotional bonds through responsive and personalized two-way communication. Previous studies indicate that digital marketing, content quality, and customer experience significantly influence engagement and loyalty. The proposed model highlights that creative content does not directly create loyalty but enhances customer engagement, which is reinforced by active online interaction. The combination of both elements creates a complementary relationship: content establishes brand identity and interest, while interaction fosters emotional closeness and trust. The findings emphasize that integrating consistent creative content with meaningful online interaction enables SMEs to improve customer retention, strengthen brand identity, and build long-term loyalty.